(untitled) (Journal of the College of Basic Education, 2026)
The current research aims to identify the effect of the inquiry learning strategy on middle school female students’ literary achievement and the development of their creative thinking. To verify the research objective, the researcher formulated the following null hypothesis: 1-There is no statistically significant difference, at the level of (0.05), between the average scores of students in the experimental group who study literature and texts using the inquiry learning strategy and the average scores of students in the control group who study literature and texts using the traditional method on the literature and texts achievement test. 2- There is no statistically significant difference, at the level of (0.05), between the average scores of students in the experimental group who study literature and texts using the inquiry learning strategy and the average scores of students in the control group in creative thinking toward literature and texts.The research sample consisted of (56) female students from the fifth literary grade at Al-Ishaqi Girls’ Secondary School, affiliated with the Salah al-Din Education Directorate/Al-Ishaqi Education Department, for the academic year (2024-2025). The students were randomly selected to implement the experiment, with Section (A) representing the experimental group with (28) students, and Section (B) representing the control group with (28) students.The researcher rewarded the two research groups (experimental and control) on the following variables: )the students’ chronological age calculated in months, their Arabic language scores for the previous academic year, the linguistic ability test, the intelligence test, and the creative thinking test(.The researcher also prepared two tools: (the achievement test and the creative thinking test(. In light of the results, the researcher reached a number of conclusions, including that the "inquiry learning" strategy made the learner a central focus of the learning and teaching process, leading to positive interaction and active participation during the lesson. The researcher also recommended adopting the inquiry learning strategy in teaching literature at the intermediate level.